MASIH RENDAHNYA KEBERTERIMAAN TEKNOLOGI DIGITAL PADA GURU DI PENDIDIKAN VOKASIONAL - Wahyuni, Nur (Jurnal Socia Akademika, 2023)
Digital transformation in the era of the Industrial Revolution 4.0 has implications for teachers in developing electronic-based learning processes that are integrated with cyber systems. The main consequence is that teachers must have a good acceptance of digital technology to manage or develop learning innovations based on the Industrial Revolution 4.0. Digital technology has five levels of acceptance, namely: awareness, literacy, capability, creativity and critical. This study analyzes the extent of the level of acceptance of digital technology owned by vocational education teachers by referring to the taxonomy of technology acceptance, namely the level of care, level of literacy, level of capability, level of creativity and critical level in using technology. This research is quantitative descriptive research with a sample of 112 vocational teachers who teach productive subjects. The data collection method used a 4-point Likert scale questionnaire developed based on indicators of each level of technology acceptability. The results showed: (1) the level of awareness of digital technology has a percentage of 83.08%; (2) the digital technology literacy level has a percentage of 66.32%; (3) the level of capability using digital technology has a percentage of 39.28%; (4) the level of creativity using digital technology has a percentage of 21.92%; and (5) the critical level using digital technology has a percentage of 20.84%. Based on these results, it can be concluded that the capability of vocational teachers to use digital technology is still in the low category so it is necessary to hold a training program using digital technology for learning